2010
DOI: 10.1007/s00418-010-0727-5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of BrdU label-retaining dental pulp cells in growing teeth and their regenerative capacity after injuries

Abstract: Recent studies have demonstrated that human dental pulp contains adult stem cells. A pulse of the thymidine analog BrdU given to young animals at the optimal time could clarify where slow-cycling long-term labelretaining cells (LRCs), putative adult stem cells, reside in the pulp tissue. This study focuses on the mapping of LRCs in growing teeth and their regenerative capacity after tooth injuries. Two to seven peritoneal injections of BrdU into pregnant Wistar rats revealed slow-cycling long-term dense LRCs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
2
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 42 publications
(51 reference statements)
9
45
2
3
Order By: Relevance
“…The present immunohistochemistry for nestin confirmed that nestin is valuable as a differentiation marker for odontoblasts (26). Furthermore, our double immunohistochemistry for nestin and Dsp proteins clearly demonstrated that the timing of their expressions in the odontoblast-lineage cells was synchronized: preodontoblasts began to express both proteins and increased their intensity according to the progress of odontoblast differentiation, and finally mature odontoblasts showed intense expression of both proteins in their cytoplasm.…”
Section: Nestinsupporting
confidence: 80%
See 2 more Smart Citations
“…The present immunohistochemistry for nestin confirmed that nestin is valuable as a differentiation marker for odontoblasts (26). Furthermore, our double immunohistochemistry for nestin and Dsp proteins clearly demonstrated that the timing of their expressions in the odontoblast-lineage cells was synchronized: preodontoblasts began to express both proteins and increased their intensity according to the progress of odontoblast differentiation, and finally mature odontoblasts showed intense expression of both proteins in their cytoplasm.…”
Section: Nestinsupporting
confidence: 80%
“…The present study clearly demonstrated that the expression of Dsp mRNA coincided with the odontoblast secretory activity for dentin matrix deposition in both 3-week-old incisors and developing molars, judging from the previous data: the rate of dentin deposition in the medial coronal portion almost ceases after 60 days in rats (57) and the progress of dentinogenesis in mice is faster than that in rats (26,27). In contrast, other pulpal cells, predentin matrix and dentinal tubules showed positive reactions only for Dsp protein and increased in their intensity according to the progress of tooth development.…”
Section: Dspsupporting
confidence: 78%
See 1 more Smart Citation
“…Inactivation of IGF-1R and p38 MAPK by their respective inhibitors, sc204008 and PD169316, induced Ki67 in DPCs ex vivo and decreased the quiescence of PY low and G0-arrested human DPSCs cells in vitro, demonstrating that p38 MAPK and IGF-1R are responsible for the mitotic quiescence of these cells. The identity of DPSCs was corroborated by their phenotype, stem cell activity, and localization of Ki67-positive cells perfectly matching the position of BrdU-positive DPSCs reported by Téclès et al [4] and Ishikawa et al [19] and the position of Oct4-positive pluripotent DPSCs reported in another study [74]. Taken together, our data establish that IGF-1R and p38 MAPK signaling pathways control human DPSC quiescence and demonstrate that these pathways must be inactivated for mitotic division to occur in DPSCs.…”
Section: Discussionsupporting
confidence: 84%
“…A study based on the mRNA expression levels of DPSC markers, including CD166, CD146, and CD105, concluded that in rat molars, ''coronal pulp harbors more SCs than the other regions'' [17]. A study by Ishikawa et al [18,19] determined that 5-bromo-2¢-deoxyuridine (BrdU)-retaining cells expressing the mesenchymal stem cell marker CD146 were associated with vessels located in the central region of adult rat dental pulp. These label retaining cells (LRCs) possessed proliferative capacity and were responsible for the regeneration of damaged odontoblasts.…”
Section: Introductionmentioning
confidence: 99%